REPRESENTASI SIKAP NASIONALISME DALAM SINEMA INDONESIA (Studi Peran Komunikasi Massa Modern Film “Darah dan Doa”) - Henricus Hans (SEMIOTIKA: Jurnal Komunikasi, 2015)
Nationalism Indonesia was formed through a complex path with a relatively long time. An understanding of nationalism itself one of which can be understood through the medium of film. Here, a film as a product of modern art becomes a medium in conveying the message directed to the audience. Through the footage presented in a film, audiences are invited to enter a world that is commonly referred to "sedondhand reality" so as to understand the messages conveyed through the medium of film. This study is a qualitative descriptive study with the object of study and prayer Blood movie director Usmar Ismail made on 30 March 1950. Analysis of data using semiotic methods Metz. The results showed that the film The Long March is a film that journey of human life during the revolution in the sacrifice of body and soul, making manifest the attitude of nationalism. Nationalism embodied in the struggle against the invaders and our own people to maintain independence in 1948. The nationalist attitude soldier held high, soldiers sacrificed body and soul, so the psychological and physical suffering. The film The Long March is a means of modern media of communication which functioned to propagate nationalism. The reason is, because of the presence of the film as a medium of communication most effectively convey nationalism education to the community. Nationalism film The Long March is racial-republican, who represents the spirit of the era of nationalism during 1948 to maintain independence. Racial nationalism can be seen through the scenes of the film on the events experienced by movie characters in the struggle against the invaders and the inner struggle (the struggle with love and suffering against the invaders and the nation itself). From these events form the theme which in all honesty was sacrificed body and soul is a picture of the reality of man in his life to be honest and willing to sacrifice body and soul for the country. Keywords: Representation, Nationalism, Film.